Antibacterial Activity of a Novel Sesquiterpene Coumarin from Ferula sinaica - A. EL-BASSUONY, ASHRAF (Asian Journal of Chemistry, 2010)
Ferulsinaic acid (1), a novel sesquiterpene coumarin has been isolated from the roots of Ferula sinaica. The structure elucidation was determined by HRMS, 1H and 13C 1D and 2D NMR spectral data.